A Study On The Impact of The Digital Economy on China’s Carbon Neutrality Capability - Wu, Shangxu (Transactions on Economics, Business and Management Research, 2024)
The digital economy is a new economic form driven by digital technology, which contains green and low-carbon effects and can promote the transition to a resource-saving and environmentally friendly society. This paper explores the impact of the digital economy on carbon neutrality capability using panel data from 30 provinces in China between 2013 and 2021and finds that the digital economy has a positive effect on carbon neutrality capability with non-linear characteristics. It has a positive and then a negative effect on carbon reduction capability, as well as a positive effect on carbon removal capability. The digital economy can aid various societal actors in enhancing carbon neutrality capability by promoting corporate technological innovation, encouraging public green consumption, and adjusting government environmental regulations.